2020
DOI: 10.11604/pamj.2020.36.363.17866
|View full text |Cite
|
Sign up to set email alerts
|

Socio-demographic, pattern of presentation and management outcome of breast cancer in a semi-urban tertiary health institution

Abstract: Introduction breast cancer is the most common malignancy in females worldwide and a major cause of cancer-related deaths in both developing and developed countries. The objective of this study was to determine the socio-demographics, pattern of presentation and management outcome of breast cancer patients. Methods clinical records of confirmed breast cancer patients between January 2011 and December 2015 at the Ekiti State University Teaching Hospital, Ado-Ekiti, Nigeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 17 publications
5
26
0
Order By: Relevance
“…The age distribution of patients reported in this study ranges from third to seventh decades of life. This is in consonance with the findings of Olaogun et al [26]. This study however, reported increased incidence amongst patients within the third decade of life.…”
Section: Yearsupporting
confidence: 93%
See 1 more Smart Citation
“…The age distribution of patients reported in this study ranges from third to seventh decades of life. This is in consonance with the findings of Olaogun et al [26]. This study however, reported increased incidence amongst patients within the third decade of life.…”
Section: Yearsupporting
confidence: 93%
“…The current study reported progressive increase in incidence from 2015 to 2019. This agrees with the findings of Olaogun et al [26] (who reported increased breast cancer incidence in Nigeria from 15.3 per 100,000 in 1976 to 64.6 per 100,000 in 2012) and Azubike et al [27]. The increased number of presented cases may be connected to increased awareness of the disease burden among the sub-urban population.…”
Section: Yearsupporting
confidence: 91%
“…in stages III and IV, suggesting the patients presented late to the hospital as was observed in a study carried out in Western Nigeria (Olaogun et al, 2020).…”
Section: Study Of Sialic Acids Level In Breast Cancermentioning
confidence: 50%
“…Several breast cancer treatments are currently in use but are more effective when the disease is diagnosed early in patients (Ali et al, 2016). Unfortunately, most women in Sub Saharan Africa present the disease to the hospital during the later stages of the disease (Olaogun et al, 2020). Breast cancer is a heterogeneous disease associated with several risk factors (Seiler et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Presentation at an advanced stage is common in low-income and middle-income countries (LMICs), and treatment outcomes are poor due to late detection, insufficient diagnostic equipment, and inadequate access to health care. [2][3][4] Therefore, efforts geared at improving early diagnosis will be worthwhile.…”
Section: Breast Cancer Screening: Can the Ibreastexam Bridge The Gap?mentioning
confidence: 99%